Synthesis and characterization of VO2-based thermochromic thin films for energy-efficient windows - Batista, C. (2011)
Thermochromic VO2 thin films have successfully been grown on SiO2-coated float glass by reactive DC and pulsed-DC magnetron sputtering. The influence of substitutional doping of V by higher valence cations, such as W, Mo, and Nb, and respective contents on the crystal structure of VO2 is evaluated. Moreover, the effectiveness of each dopant element on the reduction of the intrinsic transition temperature and infrared modulation efficiency of VO2 is discussed. In summary, all the dopant elements–regardless of the concentration, within the studied range– formed a solid solution with VO2, which was the only compound observed by X-ray diffractometry. Nb showed a clear detrimental effect on the crystal structure of VO2. The undoped films presented a marked thermochromic behavior, specially the one prepared by pulsed-DC sputtering. The dopants effectively decreased the transition of VO2 to the proximity of room temperature. However, the IR modulation efficiency is markedly affected as a consequence of the increased metallic character of the semiconducting phase. Tungsten proved to be the most effective element on the reduction of the semiconducting-metal transition temperature, while Mo and Nb showed similar results with the latter being detrimental to the thermochromism.